Correction: Expected values for pedometer-determined physical activity in older populations - Hart Teresa L; Tudor-Locke Catrine; Washington Tracy L (International Journal of Behavioral Nutrition and Physical Activity, 2009)
Abstract Correction to Tudor-Locke C, Hart TL, Washington TL: Expected values for pedometer-determined physical activity in older populations. International Journal of Behavioral Nutrition and Physical Activity 2009, 6:59